John W. Hayes and Kathleen Warner Slane, Late Classical, Hellenistic, and Roman Pottery (Isthmia XI). - Bes, Philip (Journal of Greek Archaeology, 2023)
pp. xxxii + 266, 7 plans (1 colour), 93 figures, 37 plates. Princeton: American School of Classical Studies at Athens, 2022. ISBN 978-0-87661-916-2, hardback £130.